Revisiting the musical reminiscence bump: insights from neurocognitive and social brain development in adolescence - Kudaravalli, Rishitha; Kathios, Nicholas; Loui, Psyche; Davidow, Juliet Y. (Frontiers in Psychology, 2024)
Music listening is enjoyed across the lifespan and around the world. This has spurred many theories on the evolutionary purpose of music. The Music for Social Bonding hypothesis posits that the human capacity to make music evolved for the purpose of creating and preserving relationships between one another. Considering different time periods of music use across the lifespan, adolescence is especially a period of social reorientation away from family towards peers, characterized by new social bonds and increased prosocial behavior. This shift is accompanied by notable structural and functional changes in brain networks supporting reward processing and prosocial behavior, such as the "social brain" and the reward system. Reviewing the extant literature on developmental cognitive neuroscience and adolescent music use, we propose that neurocognitive changes in the reward system make adolescence an ideal developmental time window for investigating interactions between prosocial behavior and reward processing, as adolescence constitutes a time of relative increase in music reward valuation. Testing this hypothesis may clarify our understanding of developmental trajectories in music reward valuation, and offer insights into why music from adults' adolescence holds a great deal of personal significance.